E-Application System For Sabk Maahad Ehyak Diniah Islamiah - Mahadi, Hanis Nadiah; Dahlan, Azlin; Hasnan, Mazliana (2020)
Sekolah Agama Bantuan Kerajaan (SABK) Maahad Ehyak Diniah Islamiah is a boarding school with around 500 students located in Perak. The school processes around 350 new application forms for Form 1 intake annually. However, the application process is tedious for both parents and teachers because it is done manually. The parents will come to the school office to get the application form, fill out the form and come back to the school to return the form including attachment of relevant documents. The teachers need to go through the application form one by one to shortlist the candidates that fulfill the academic requirements and then transfer the details from the form into Microsoft Excel. In view of the situation, an online application system has been developed to tackle the problem by using the Waterfall Model as the methodology, PHP with Laravel framework as the language and MySQL as the database. The system allows parents to apply online and the system checks the academic qualification automatically, provides the application status to the applicants whether qualified for a qualification test or not and lists the shortlisted candidates. The system relieves the parents from having to travel a few times to the school and relieves the teachers from the tedious and meticulous tasks of checking the candidates’ academic background. However, several future works need to be done, with the most important is to provide features to upload attachments and to generate automatic offer letters.